DAMPAK MANAJEMEN SUMBER DAYA MANUSIA DAN MOTIVASI TERHADAP KINERJA KARYAWAN MELALUI VARIABEL INTERVENING KOMITMEN ORGANISASI - Bambang Aviantono (Jurnal Cakrawala Ilmiah, 2022)
This research study aims to examine the effect of human resource management (HRM) policies and motivation on employee performance with organizational commitment as an intermediate or intervening variable in 5 MSME companies in Mustika Jaya sub-district, Bekasi, West Java. This study includes HR policy factors and motivation as independent variables while employee performance factors as the dependent variable. Furthermore, this study aims to determine the role of "organizational commitment" as an intervening variable between policy (HRM) and motivation on employee performance, and within the framework to achieve this goal, the researcher uses a descriptive analytical (quantitative) method which represents using outer inner loading analysis to verify the strength of the structural model of the study factor using (SEM-PLS). This study targets all employees who work in 5 MSME companies specifically for micro trade. This study has concluded with many results, and one of the most important results is, there is a positive relationship between (HRM) and motivation on employee performance. The results also found that there was a positive direct or indirect effect on employee performance through organizational commitment with a moderate percentage achieved from direct and indirect effects